ACUTE LEUKEMIA IN CHILDREN - AN INPATIENT DESCRIPTIVE STUDY - AHMAD, A; SALAHUDDIN, A; AHMAD, S (Biological and Clinical Sciences Research Journal, 2023)
Acute leukemia in children causes unacceptably high morbidity and mortality in the affected patients in our population. This study was undertaken to create local data that could be used to better understand the characteristics of this disease in our set up, provide better management to the affected children and help decrease the high morbidity and mortality associated with this disease. To determine the frequency of the significant classes of acute leukemia, its subclasses and rate of remission in our study population. This study was conducted in Pediatric B Unit, Department of Pediatrics, Hayatabad Medical Complex, Peshawar, from 1st June 2017 to 31st December 2018. Using consecutive sampling technique, 90 cases were selected. All children who underwent bone marrow examination during the study period in this hospital were included in the study. Data on age, gender, indications, and major types and subclasses of leukemia was extracted from bone marrow record forms of these children and analyzed using SPSS version 20. Means and standard deviations were calculated for age and frequency and percentages for gender, types, and subtypes of leukemia and remission. 90 patients were included in this study. TLC was low in 33 (36.7%). Normal in 24 (26.6%) and raised in 33(36.7%). Acute lymphoblastic leukemia- ALL -L1 accounted for 80 (88.9%) of cases, while acute myelogenous leukemia for 10(11.1%). Acute myelogenous leukemia subtypes included AML-M5 in 5 (5.6%), AML-M2 and AML-M3 (2.2%) AML-M0 2 (2.2%), and AML-M2 1 (1.1%). 43 (47.8%) were newly diagnosed cases. 47 (52.2%) were previously diagnosed cases, of which 26 (55.3%) were in remission. Acute lymphoblastic leukemia ALL-L1 was the commonest type of leukemia with ALL-L1 subtype in all patients followed by acute myelogenous leukemia with AML-M5 the commonest subtype. Rate of response to therapy was 55.3%.